The digital transformation of the tax administration services as a mechanism for strengthen tax control in Algeria: a case study of the Blida Tax Centre using the structural equation model - Bachari, Selma (Journal of Excellence for Economics and Management Research, 2026)
Digital transformation is one of the most important strategies employed to increase the effectiveness of tax control in countries that suffer from low ordinary taxes and an inefficient tax collection like Algeria. In this context, this research paper aims to analyze the impact of digital transformation on the effectiveness of tax control in Algeria. Given the scarcity of published statistics on the subject, we conducted a survey using a questionnaire addressed to employees and managers in charge of the tax control process in the tax center of the province of Blida. Using structural equation modeling with SmartPLS4 software, we were able to estimate the model and analyze the direct and indirect effects between the study variables. The results showed that digital transformation has a positive significant direct impact on formal tax control, but not on in-depth control. The results concluded that digital transformation has an indirect positive impact on the effectiveness of tax trough the formal tax control. Therefore, it will be better to strength the digital transformation process to include various in-depth control operations and not only the formal control of companies’ tax documents via the digital platform.